Spatio-temporal patterns in pelagic fish school abundance and size: a study of pelagic fish aggregation using acoustic surveys from Senegal to Shetland - Beare, Douglas; Reid, D.G.; Petitgas, Pierre; Carrera, Pablo; Georgakarakos, Stratis; Haralabous, John; Iglesias, Magdalena; Liorzou, Bernard; Muiño, Ramón (2000)
As part of the EU funded project CLUSTER, databases were constructed of pelagic fish schools identified during a series of acoustic surveys in the NW North Sea, Bay of Biscay, western Mediterranean and Agean Seas and off Senegal. Among other descriptors, the databases usually included the height, length and energy (S,,) of each school. The number of schoo!.s per 1 nmi EDSU was also recorded. The relationship between these descriptors and a range of external variables (eg bottom depth, time of day and location) were examined using a suite of multiple regression models. The results indicate strong non-linear dependencies in some of the surveys on time of day and water depth. School count per EDSU tended to be high during the middle part of the day and lower at dawn and dusk. Furthermore, the ‘shape’ of this dependence on time of day is non-constant and changes with location and year. Possible explanations for such patterns and the differences and similarities between the survey areas will be discussed, as well as the impact of these findings on the conduct and analysis of acoustic surveys. In addition, we have examined the spatio-temporal pattern of sampling in each of the survey series and we will present an analysis of the impact of survey design on the potential for such spatio-temporal modelling studies.